RI 9525 - Studies of Stope-Scale Seismicity in a Hard-Rock Mine - Part 1: Methods and Factors - Robert L. Kranz (The National Institute for Occupational Safety and Health (NIOSH), 2010)
The U.S. Bureau of Mines (USBM) has been monitoring and studying seismic activity associated with mining in the Coeur d'Alene silver district of northern Idaho. New statistical methods of studying the stope-scale (1-to l00-m) seismicity at one Idaho silver mine are used in this report (part 1) and its companion (part 2). This report deals with methodology and its limitations. The recent concept of fractals and their seismological use is discussed and applied to mining-induced seismicity. Three types of fractal studies are addressed: spatial analyses (including temporal changes of spatial patterns), temporal analyses, and size analyses. Other statistical measures of mine seismicity are also addressed: event mean location, inter-event distance distribution skewness, temporal coefficient of variation, nearest neighbor and next event statistics, and event location planarity patterns. Each of the methodologies discussed (fractal and nonfractal) is presented using sample data from two stopes in the mine. It is shown that stope-scale, mining-associated microseismicity has a fractal nature. The usefulness of demonstrating fractality (scale invariance) for predictive or descriptive purposes depends on recognition of the factors affecting the calculation of fractal dimensions. Several methodological traps are illustrated that can lead to an incorrect conclusion.